Control of coordination polymerization behavior by counter-anionic effects - Tanaka, Ryo; Ajala, Oluwaseyi Aderemi; Nakayama, Yuushou; Shiono, Takeshi (Progress in polymer science, 2023)
In coordination polymerization chemistry, the most active species are cationic transition metals which bear vacant sites for monomer coordination. The steric and electronic properties around the metal center are strongly related to the polymerization behavior. Thus, the development of the catalyst system mainly represents the design of neutral metal complex precursors, especially the structure of the ligand. On the other hand, the choice of counteranions derived from the cocatalysts sometimes plays a crucial role in the controlled coordination polymerization. Some unusual polymerization behaviors on stereospecificity, activity, and monomer reactivity ratios have been reported by designing the structure of these cocatalysts. The review summarizes these examples of polymerization controlled by cocatalysts. Various cocatalysts, such as methylaluminoxane (MAO), fluoroarylboranes, and borates with different activation mechanisms, are introduced based on their structural analysis and molecular design. Heterogeneous cocatalysts, important for industrial applications, are also mentioned with their various characterization methods. The application of these cocatalysts is discussed, along with the introduction of several techniques evaluating the relationship between cocatalysts and polymerization behavior. Moreover, the counter-anionic effect in the late-transition metal-catalyzed polymerization chemistry, which recently attracted many researchers for its versatile applicability for polar monomers, is reviewed. [Display omitted]